PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM DENGAN PERDAGANGAN SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR FOOD & STAPLES RETAILING DI BURSA EFEK INDONESIA PERIODE 2018 -2023 - Surono, Yunan; Wuri Lastari, Adria; Helencia, Kiki; Zuvilla Irwanto, Telly (Fakultas Hukum dan Ekonomi Bisnis, 2024)
This study aims to find out and analyze the influence of financial performance variables on stock prices with stock trading variables as an intervening variable in companies in the food & staples retailing sector on the Indonesia Stock Exchange for the period 2018 – 2023. Data, facts and information obtained from the issuer's financial statements show that the total value of assets, current assets, fixed assets, total debt, short-term debt, long-term debt, sales, gross profit, operating profit, net profit, total equity. Data analysis in this study uses Partial Least Square (PLS-SEM), with Smart PLS 4.0 software. The results of the study show that 1) Financial performance variables with DAR and DER indicators have an effect on stock price variables in companies in the food & staples retailing sector on the Indonesia Stock Exchange. 2) Financial performance variables with DAR and DER indicators have no effect on stock trading variables with FREKW PDG and PDG NILAI indicators in food & staples retailing sector companies on the Indonesia Stock Exchange. 3) Stock trading variables have no effect on stock price variables in companies in the food & staples retailing sector on the Indonesia Stock Exchange. 4) Financial performance variables have no effect on stock price variables with stock trading as an intervening variable